Complete pathway elucidation of echinacoside in Cistanche tubulosa and de novo biosynthesis of phenylethanoid glycosides - Wenqian Huang; Yaru Yan; Weisheng Tian; Xiaoxue Cui; Yingxia Wang; Yuelin Song; Ting Mo; Xiping Xu; Saijing Zhao; Yuyu Liu; Xiaohui Wang; Juan Wang; et al. (Nature Communications)
Abstract Echinacoside (ECH), one of the most representative phenylethanoid glycosides (PhGs), has considerable neuroprotective effects and is an effective ingredient in numerous commercial drugs. Here, we elucidate the complete ECH biosynthetic pathway in the medicinal plant Cistanche tubulosa. In total, 14 related genes are cloned and functionally characterized. Two upstream pathways for tyrosol biosynthesis from L-tyrosine are identified: one includes separate decarboxylation, deamination and reduction steps; the other uses microbial-like transamination, decarboxylation and reduction steps. In addition, a distinct downstream assembly process from tyrosol to ECH is revealed that includes sequential glucosylation, acylation, hydroxylation, and rhamnosylation to form acteoside, and ends with a final glucosylation converting acteoside to ECH. Furthermore, the de novo synthesis of 23 PhG derivatives is achieved via the heterologous expression of different combinations of the functional genes in tobacco. Our findings provide insights into the biosynthesis of ECH and a platform for alternative production of complex PhGs.